An Analysis of Slang in Benjamin Zephaniah’s Selected Songs - Yoan Andino; Hermawati Syarif (English Language and Literature, 2021)
Slang is the most informal form of cammunication in certai communities, Yule (2006). Slang comes in different kind of varities based on the process it appear. Song is one of many media that slang could appear and exist. Some song creator include slang as one of their prefer word selection putting in the lyrics. One of the singer is Benjamin Zephaniah. Benjamin uses a lot of slang in his song. This kind of phenomenon in language, slang, interest linguists to analyze songs that have slang but only a few study in Benjamin Zephaniah works. This research analyze slangs that occur in Benjamin Zephaniag songs using theory of language varities by Yule. There are six types of slangs that exist in Benjamin’s selected songs. Most common slang are coinage and multiple process. The goal of Benjamin using slang on his works are to show his identitiy as african born and to show his hate against racism.